Methane Control of Adventitious Rooting Requires γ-Glutamyl Cysteine Synthetase-Mediated Glutathione Homeostasis. (27th December 2018) - Jiang, Xumin; He, Junjie; Cheng, Pengfei; Xiang, Zhixin; Zhou, Heng; Wang, Ren; Shen, Wenbiao
Abstract: Although the key role of methane (CH4 ) in the induction of cucumber adventitious rooting has been observed previously, the target molecules downstream of the CH4 action are yet to be fully elucidated. Here, we reported that exogenous glutathione (GSH) induced cucumber adventitious root formation; whilel -buthionine-sulfoximine (BSO) treatment inhibited it. BSO is a known inhibitor of γ -glutamyl cysteine synthetase ( γ -ECS), an enzyme involved in GSH biosynthesis. Further investigations showed that endogenous GSH content was rapidly increased by CH4 application, which was correlated with the increased CsGSH1 transcript and γ -ECS activity. Mimicking the responses of GSH, CH4 could upregulate cell cycle regulatory genes ( CsCDC6, CsCDPK1, CsCDPK5 and CsDNAJ-1 ) and auxin-response genes ( CsAux22D-like and CsAux22B-like ). Meanwhile, adventitious rooting-related CsmiR160 and CsmiR167 were increased or decreased, respectively, and contrasting tendencies were observed in the changes of their target genes, that included CsARF17 and CsARF8 . The responses above were impaired by the removal of endogenous GSH with BSO, indicating that CH4 -triggered adventitious rooting was GSH-dependent. Genetic evidence revealed that in the presence of CH4, Arabidopsis mutants cad2 (a γ -ECS-defective mutant) exhibited, not only the decreased GSH content in vivo, but also the defects in adventitious root formation, both of which were rescued by GSH administration other than CH4 . Together, it can be concluded that γ -ECS-dependent GSH homeostasis might be required for CH4 -induced adventitious root formation.